The TFIIIA recognition fragment d(GGATGGGAG).d(CTCCCATCC) is B-form in solution. - Aboul-ela, F (1988)
The deoxyoligonucleotide d(GGATGGGAG).d(CTCCCATCC) is a portion of the gene recognition sequence of transcription factor IIIA (TFIIIA). The crystal structure of this oligonucleotide was shown to be A-form (Mc Call, M., Brown, T., Hunter, W.N., and Kennard, O. 1986 Nature 322, 661-664). The present study employs NMR, optical, chemical and enzymatic techniques to investigate the solution structure of this DNA 9-mer. NMR COSY experiments indicate 16 of the 18 residues are predominantly south (C2'-endo) sugar conformation. NMR NOESY indicates glycosidic angles in the range predicted for B-form DNA as opposed to A-form. Related DNA and RNA self-complementary 18-mer sequences, d(GGATGGGAGC-TCCCATCC), with U substituted for T in RNA, were studied by circular dichroism. CD spectra support B-form structures for the DNA 9-mer and the DNA 18-mer, and A-form for the RNA 18-mer. High trifluoroethanol concentrations induce a B- to A-form transition in the DNA oligonucleotides. Enzymatic and chemical probes also illustrate significant differences between the DNA and the RNA oligonucleotides. We find no evidence to support an A-form conformation for the TFIIIA recognition sequence d(GGATGGGAG).d(CTCCCATCC) in solution.